Agile Governance in the Implementation of the Electronic Based Government System (SPBE) in the City of Banda Aceh: Agile Governance dalam Penyelenggaraan Sistem Pemerintahan Berbasis Elektronik (SPBE) Kota Banda Aceh - Rozalia Wardana; Ismail Nurdin; Ela Lesmanawaty Wargadinata (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to analyze the implementation of Agile Governance in the digital governance of the Banda Aceh City Government, particularly in the administration of the Electronic Based Government System (SPBE), to identify strategic factors influencing its implementation, and to formulate acceleration efforts to strengthen organizational adaptability. Methodology: This study employed a qualitative approach with a case study design. Data were analyzed using thematic coding assisted by NVivo 15 Plus and interpreted based on six principles of Agile Governance. Data saturation was achieved following theoretical sufficiency across all six principles. Findings: The findings show that the implementation of Agile Governance in Banda Aceh has been reflected in digital service development, public service responsiveness, adaptive service management, and acceleration efforts through system integration, infrastructure strengthening, and digital capacity building. The SPBE score improved from 2.24 (2019) to 3.70 (2024), demonstrating gradual progress. Implementation is supported by leadership commitment, SPBE policy framework, inter-agency collaboration, technical capacity, and digital infrastructure. However, challenges remain in inter-agency system integration, technical human resource capacity, organizational coordination, and cross service data management. Practical Implication: This study provides practical direction for local governments to strengthen Agile Governance   through digital service integration, enhancement of technical human resource capacity, cross agency coordination, and more responsive evaluation of digital public services. Originality: The study highlights that Agile Governance in local government evolves as a gradual adaptive process shaped by organizational capacity, institutional arrangements, and public service orientation.